Review of Zakat From The Perspective of Philosophy Of Science - Indra Utama; Mugi Harsono (Journal of Economic Education, 2023)
Zakat is the obligation of every Muslim who has fulfilled the nishab and haul requirements. Zakat has been practiced since the Prophet Muhammad SAW to today's contemporary zakat. This study aims to discuss zakat from the perspective of the philosophy of science in the dimensions of ontology, epistemology, and axiology. This research uses a qualitative, descriptive approach and literature study. Data were obtained from reference articles searched through the Google application and Published or Perish. The results of the study show that from the perspective of the philosophy of science, zakat can be explained in three dimensions, namely: ontology, epistemology, and axiology. On the ontological dimension, zakat includes the meaning of the nature of the science of zakat which can be proven to exist. The epistemological dimension of the science of zakat related to the basis of knowledge, sources, characteristics, truth of knowledge, and how to obtain zakat knowledge. Finally, on the axiological dimension, the discussion of zakat includes the relationship between knowledge and values, the feasibility of the science of zakat to be developed, and the functions and uses of the science of zakat. In the end, the science of zakat needs to be developed so that the benefits of zakat are more significant for the welfare of society.